A low traffic overhead transmission power control for wireless body area networks - Fernandes, Duarte Manuel Azevedo (2018)
Wireless body area networks are being deployed for an ever increasing number of applications. The main research challenges are still related to the quality of the communication link and to the energy consumption. Since WBAN on-body communication channels' quality varies over time, it is not appropriate to use a static and pre-defined transmission power level (TPL). Nowadays, the vast majority of WBANs use transmission power control (TPC) mechanisms aiming to minimize energy waste during on-body communications, radio interferences, and the energy specific absorption rate (SAR). These goals are achieved by continuously adjusting and updating the TPL. This paper proposes a novel TPC mechanism that employs a hybrid operation principle (closed-loop control together with posture and motion detection) targeting resource constrained devices. This mechanism uses the on-body communication RSSI values to approximate the fading signal during the user's gait cycle and, simultaneously, the acceleration signal (from inertial sensors) is used to determine the position within the gait cycle. Experimental results shows that the proposed TPC mechanism is capable to achieve up to 35% energy save per packet transmitted compared with the transmissions performed at maximum TPL. Furthermore, the additional traffic overhead is significantly smaller than those verified in other TPCs addressed in the literature. This research shows that all WBAN application requirements identified by IEEE 802.15.6 TG can be ensured in an energy-efficient way without sacrificing reliability and latency.